Hard Rain: Annie McIntyre # 2 - Allen, Samantha Jayne (New York : Minotaur Books, 2023)
"From the Tony Hillerman Prize-winning author of Pay Dirt Road comes Hard Rain, Samantha Jayne Allen's mesmerizing next novel set in a hardscrabble Texas town dealing with disaster. In shock and found clinging to a tree branch, Bethany Richter is pulled from thrashing floodwaters that have decimated the town of Garnett, Texas and killed a dozen others. Six months after solving the murder of a local waitress, Annie McIntyre is working as an apprentice P.I. when she's handed her first solo case: uncover the identity of the man who rescued Bethany before he was swept downriver. When Annie's search turns up a different victim-shot dead, not drowned-Annie questions if the hero they seek is actually a killer. Flexing her new skills while relying on the wisdom of her eccentric, ex-cop grandfather, the case leads Annie into a web of drug dealers, preachers, and wayward drifters trying to make sense of life after a disaster. Annie's own convictions are put to the ultimate test as long-held secrets, corruption, and violence are exposed like the ruin that lies beneath receding waters"--.
new book 2023 spring.
Keywords: Mystery and Detective; Floods; Murder -- Investigation; sex and gender; Detective and mystery fiction; Novels; Detective fiction; Mystery fiction